PERSEPSI PEDAGANG KAKI LIMA TERHADAP PENERTIBAN YANG DILAKUKAN OLEH PEMERINTAH KOTA PEKANBARU (Studi Di Jalan HR. Soebrantas Kecamatan Tampan) - Andriani, Feni; Yusuf, Yusmar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research is to study analyzes the views and strategies of Street Vendors of the demolition carried out by the municipality of Pekanbaru. Is a social phenomenon that occurs in people who have low income as street vendors (Informal Sector) at HR. Soebrantas. The theory used is the theory of perception, rational action and social capital. The data analysis was done by descriptive qualitative data collection techniques in this research is purposive in which the number of informants numbering 10 people consisting of hawkers, pp municipal police and the consumer. From the results of research in the field that the perception of street vendors (Informal Sector) give a good response, demolition is done is correct and good, while the response is not good from the merchant is to say demolition is done is not good because of evictions uneven. In conducting trade activities of traders has a coping strategy in facing demolition by performing resistance or resistance, resistance is done in two ways, among others, resistence to open and covert resistenceKeywords: Street Vendors (Informal Sector), Perception, Strategy